Metodologia para escolha do tipo de fresa para faceamento de acabamento - Gobbi, Lucas Ganzer (2022)
Machining is a manufacturing process very present in the metalworking industry. Most products that involve metal, at some part of their manufacture, go through some machining process. Within the defined geometry machining processes is the milling process, which is the second most used in the industry. Many authors have developed works that evaluate different tools for milling, taking into account only factors such as surface finish and tool life. However, not always only these factors are taken into account when choosing the tool within the industry. In view of this, the present work aims to compare cutting tools of different geometries used in face milling under different machining conditions and to propose a method to aid decision making that allows indicating the best combination of parameters and insert for face milling. The face milling experiments were carried out on ABNT 1045 steel blocks, using two cutting inserts of different geometry and two feeds per cutting edge. Roughness data were obtained using a roughness meter and the maximum flank wear was obtained using a stereoscopic microscope. The method Direct Rating was applied for the weighting of criteria and the TOPSIS method for sorting the alternatives. The criteria analyzed considered aspects related to quality, productivity, f lexibility and costs involved in face milling. It was observed that the alternative of milling with round insert and lower feed per edge was the best ranked. Among the advantages of this alternative are lower roughness and longer insert life. The result coherently expressed the best alternative according to the decision-makers’ objectives. Finally, it appears that the method broadly evaluated the technical and economic aspects of the face milling process.